Influence of zinc on CTX-M-1 β-lactamase expression in Escherichia coli. (September 2020) - Peng, Shifu; Herrero-Fresno, Ana; Olsen, John E.; Dalsgaard, Anders
Highlights: The use of antimicrobial growth promoters has been banned in the European Union. Zinc oxide has been widely used as feed supplements to improve growth in post-weaning pigs. Zinc oxide affects the growth of multi-antimicrobial-resistant bacteria. Zinc oxide is associated with the antimicrobial-resistance genes in human pathogens. Abstract: Objective: Zinc oxide is used to prevent post-weaning diarrhoea in pigs as an alternative to antimicrobial growth promoters. This study aims to determine if the use of zinc oxide selects for extended-spectrum β-lactamase (ESBL)-producing Escherichia coli and affects the expression of bla CTX-M-1 in E. coli. Methods: Using an in vitro faecal micro-cosmos model, the selective properties of zinc were investigated using an E. coli strain with bla CTX-M-1 encoded by a natural IncI1 resistance plasmid (MG1655/pTF2) and another strain where the same gene was located on the chromosome (MG1655:: bla CTX-M-1 ). The micro-cosmos was seeded with faecal material containing an increasing concentration of zinc (0–8 mM). Outcome measurements consisted of colony-forming units (CFU) of the inoculated ESBL E. coli and naturally occurring coliforms as determined by plate counting on MacConkey with and without 5 mg/L cefotaxime as well as total viable bacteria determined on Luria agar without cefotaxime. Expression of bla CTX-M-1 under the experimental zinc concentrations was determined by quantitative polymerase chain reaction. Results: The proportion of MG1655/pTF2 of the total viable bacteria was significantly higher at high zinc concentrations (6 and 8 mM) compared with low concentrations (0–4 mM). The messenger RNA (mRNA) levels of bla CTX-M-1 in the two ESBL strains increased at increasing zinc concentrations and varied with the growth phase. Conclusion: The growth of the inoculated CTX-M-1-encoding E. coli MG1655 strains and naturally occurring coliforms was impacted differently when exposed to zinc oxide. The bla CTX-M-1 mRNA expression levels seemed to increase with increasing zinc concentrations, but varied with growth phase, but not gene location.